Short circuit current vs. cell thickness in solar cells under rear illumination: a direct evaluation of the diffusion length - Plá, Juan Carlos; Tamasi, Mariana Julia Luisa; Bolzi, Claudio Gustavo; Venier, G.L.; Durán, Julio César (Elsevier Science, 2000)
Fil: Plá, Juan Carlos. Comisión Nacional de Energía Atómica. Departamento de Energía Solar; Argentina